Mineralogical and geochemical controls of arsenic speciation and mobility under different redox conditions in soil, sediment and water at the Mokrsko-West gold deposit, Czech Republic - Drahota, Petr; Rohovec, Jan; Filippi, Michal; Mihaljevic, Martin; Rychlovský, Petr; Cervený, Václav; Pertold, Zdenek (The Science of the total environment, 2009)
Naturally contaminated soil, sediment and water at the Mokrsko-West gold deposit, Central Bohemia, have been studied in order to determine the processes that lead to release of As into water and to control its speciation under various redox conditions. In soils, As is bonded mainly to secondary arseniosiderite, pharmacosiderite and Fe oxyhydroxides and, rarely, to scorodite; in sediments, As is bonded mainly to Fe oxyhydroxides and rarely to arsenate minerals. The highest concentrations of dissolved As were found in groundwater (up to 1141 microg L(-1)), which mostly represented a redox transition zone where neither sulphide minerals nor Fe oxyhydroxide are stable. The main processes releasing dissolved As in this zone are attributed to the reductive dissolution of Fe oxyhydroxides and arsenate minerals, resulting in a substantial decrease in their amounts below the groundwater level. Some shallow subsurface environments with high organic matter contents were characterized by reducing conditions that indicated a relatively high amount of S(-2,0) in the solid phase and a lower dissolved As concentration (70-80 microg L(-1)) in the pore water. These findings are attributed to the formation of Fe(II) sulphides with the sorbed As. Under oxidizing conditions, surface waters were undersaturated with respect to arsenate minerals and this promoted the dissolution of secondary arsenates and increased the As concentrations in the water to characteristic values from 300 to 450 microg L(-1) in the stream and fishpond waters. The levels of dissolved As(III) often predominate over As(V) levels, both in groundwaters and in surface waters. The As(III)/As(V) ratio is closely related to the DOC concentration and this could support the assumption of a key role of microbial processes in transformations of aqueous As species as well as in the mobility of As.
Keywords: Environmental Pollutants; monitorování životního prostředí; látky znečišťující životní prostředí; voda; Česká republika; Environmental Monitoring; Geologic Sediments; Water; Oxidation-Reduction; Czech Republic; Arsenic; půda; Mining; geologické sedimenty; zlato; hornictví; oxidace-redukce; Gold; arsen; Soil